Empowerment Evaluation Research Trends: Bibliometric Analysis for the Years 2014 to 2023 - Hayati, Nurul; Sudiapermana, Elih; Saepudin, Asep; Adiwinata, Jajat S.; Komar, Oong; Aini, Wirdatul; Azizah, Zahratul (Universitas Negeri Padang, 2024)
Empowerment evaluation is critical in ensuring that the empowerment program achieves its goals and provides the intended benefits to the community it serves. By conducting a complete bibliometric analysis for the period 2014-2023, this study analyzed the current state and research trends in the subject of empowerment evaluation. This research focused on publication language, growth rates, keywords, most frequently used authors, most referenced papers, most prolific authors, most productive institutions, and most active countries. 355 journal articles were obtained from the Scopus database for bibliometric mapping analysis. The research findings showed that: (1) the majority of articles were written in English; (2) the most published articles were in 2015, with 65 articles; (3) empowerment was the most commonly used keyword; (4) the article by Fox, J.A. 2015 was the most frequently cited document; (5) Ponsford, R. from the London School of Hygiene & Tropical Medicine, United Kingdom (England) is the most prolific writer; and (6) the London School of Hygiene & Tropical Medicine in the United Kingdom (England) is a public institution that produces the most work in the field of empowerment evaluation; and (7) the United States is the country with the highest work productivity in this field. This paper makes an important contribution to the topic of empowerment evaluation by providing a complete overview, scientific landscape, and future directions for the advancement and strengthening of research in the field.